An in vitro assay for drug sensitivity of Trypanosoma congolense using in vitro-derived metacyclic trypanosomes - Gray, M.A.; Peregrine, A.S. (Elsevier, 1993)
The sensitivity of seven populations of T. congolense to the salts of three trypanocides, diminazene, isometamidium and homidium, were determined in vitro using in vitro-derived metacyclic trypanosomes. The trypanosomes were incubated at 35 degree centigrade for 48 hours with various drug concentrations (0.5 ng-50 ug/ml) and then transferred to cultures containing bovine endothelial-cell monolayers, to assess their viability over the following 5 days as compared to control trypanosomes that had been incubated without drug. The sensitivity to each drug was expressed as the minimum effective drug concentration which killed 100 percent of the trypanosomes in a given population within the 5 days. Using this assay, population IL 1180, characterised as being highly sensitive to all three drugs in vivo, required 10 ng/ml isometamidium chloride, 50 ng/ml homidium bromide or chloride and 5000 ng/ml diminazene aceturate to kill the entire population in vitro. In contrast, two derivatives of IL 1180 in which resistance to isometamidium had been induced in mice, IL 3343 and IL 3344, required isometamidium chloride at a concentration of 1000 ng/ml and 2000 ng/ml, respectively, to eliminate the populations. The in vitro results showed that the increase in level of resistance to isometamidium in these populations was associated with at least a 200-fold increase in resistance in both populations to homidium, but no increase in resistance to diminazene. KE 2887 and CP 81, two isolates expressing high levels of resistance to both isometamidium and homidium in mice and cattle, were both resistant in vitro to isometamidium chloride and homidium salts at 100 ng/ml. Furthermore, while the former population was resistant to 10 000 ng/ml diminazene aceturate, the latter was sensitive to 5000 ng/ml. IL 3274 and IL 3330, characterised as expressing high levels of resistance to all three drugs in vivo, were shown to be resistant to isometamidium chloirde and homidium salts at 1000 ng/ml, and to diminazene aceturate at 10 000 ng/ml. Finally, the in vitro IC 100 (concentration of drug required to eliminate 100 percent of the population) results were consistent with the maximum amounts of each drug detected in vivo.